Novel multilayer meniscal scaffold provides biomechanical and histological results comparable to polyurethane scaffolds: An 8 week rabbit study - Nihat Demirhan Demirkıran; Hasan Havıtçıoğlu; Aylin Ziylan; Ülker Cankurt; Buğra Hüsemoğlu (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the meniscal regeneration and arthritic changes after partial meniscectomy and application of either polyurethane scaffold or novel multilayer meniscal scaffold in a rabbit model. Methods: Sixteen NewZealand rabbits were randomly divided into three groups. A reproducible 1.5-mm cylindrical defect was created in the avascular zone of the anterior horn of the medial meniscus bilaterally. Defects were filled with the polyurethane scaffold in Group 1 (n:6) and with novel multilayer scaffold in Group 2 (n:6). Rabbits in Group 3 (n:4) did not receive any treatment and defects were left empty. All animals were sacrificed after 8 weeks and bilateral knee joints were taken for macroscopic, biomechanical, and histological analysis. After excision of menisci, inked condylar surfaces and tibial plateaus were evaluated for arthritic changes. Digital photographs of excised menisci were also obtained and surface areas were measured by a computer software. Indentation testing of the tibial condyles and compression tests for the relevant meniscal areas was also performed in all groups. Histological analysis was made and all specimens were scored according to Rodeo scoring system. Results: No signs of inflammation or infection were observed in any animals. A significant difference was observed between meniscus surface areas of the multilayer scaffold group (20.13 ± 1.91 mm2) and the group with empty meniscus defects (15.62 ± 2.04 mm2) (p = 0.047). The results of biomechanical compression tests revealed a significant difference between the Hayes scores of the second group (1.728) and the empty defect group (0,467) (p = 0.029). Intact meniscal tissue showed higher mechanical properties than all the defected samples. Multilayer scaffold group demonstrated the closest results compared to healthy meniscus tissue. Tibia indentation tests and histological evaluation showed no significant differences between groups (p = 0.401 and p = 0.186 respectively). Conclusions: In this study, the initial evaluation of novel multilayer meniscal scaffold prevented the shrinkage that may occur in the meniscus area and demonstrated superior biomechanical results compared to empty defects. No adverse events related to scaffold material was observed. Besides, promising biomechanical and histological results, comparable to polyurethane scaffold, were obtained. Keywords: Meniscal scaffold, Multi-layer meniscus scaffold, Composite scaffold, PHBV, Luffa Cylindirica fiber, Strontium ranelate